Dinig sana kita - Sandejas, Mike; Sandejas, Zoe; Mallari, Romalito; Agcaoili, Adriana; Cinemalaya Foundation ([Place of production not identified] Cinemalaya Foundation, 2009)
The romantic film revolved around a rocker and a deaf boy. One lives in silence while other in noise and fear. The two met in a Baguio camp where hearing kids were mixed with non-hearing kids to find their common ground, which is their love for music--https://en.wikipedia.org/wiki/If_I_Knew_What_You_Said
Produced by Mike Sandejas; music by Francis Reyes; cinematography by Albert Banzon.
Zoe Sandejas, Romalito Mallari, Adriana Agcaoili.
DVD
In Tagalog
Keywords: Drama; Romance